Atividade antimicrobiana de ácidos orgânicos e compostos clorados sobre micro-organismos patogênicos em carne de frango - Zabot, Sandra (2016)
The current scenario of the Brazilian poultry production is defined by high productivity motivated by exports to markets with elevated levels of sanitary requirement. The work aimed to evaluate the efficacy of chlorinated compounds (chlorine dioxide, dichloro and trichloro) and organic acids (citric, lactic and peracetic acids) in reducing the contamination of poultry by Salmonella spp., mesophiles and enterobacteriaceae. Were isolated 102 strains Salmonella spp. poultry carcass from June to September 2014. Strains were identified by PCR. Was determined the minimum inhibitory concentration (MIC) of antimicrobial compounds for the standard strains of S. Typhimurium, S. Enteritidis and S. Heidelberg. MIC of lactic acid and peracetic acid (20 to 10 g/L) was applied in strains of Salmonella spp. isolated from the slaughter. The MIC of the compounds lactic acid and sodium dichloro was applied in contaminated chiller water with Salmonella (109 CFU/mL) and this was determined Salmonella count in water. Thighs and drumsticks poultry were contaminated with S. Heidelberg (109 UFC/mL) and were applied dichloro (60 mg/L), lactic acid (20 g/L) and sodium hypochlorite (5,0 and 0,5 mg/L) compounds. In the identification by PCR, 93,1% of the strains were identified as Salmonella. For sodium dichloro the MIC was 60 mg/L for 15 minutes to S. Heidelberg and 60 mg/L for 20 minutes for S. Enteritidis. Lactic acid presented MIC of the 5 g/L for 10 minutes to S. Enteritidis 10 g/L for 15 minutes to S. Typhimurium and 20 g/L for 20 minutes to S. Heidelberg. For peracetic acid, MICs were 10 g/L for 10 minutes to S. Typhimurium and S. Heidelberg and 10 g/L for 20 minutes to S. Enteritidis. To citric acid, MICs were 10 g/L for 10 minutes to S. Typhimurium and S. Enteritidis and 25 g/L for 20 minutes to S. Heidelberg. In the isolated Salmonella strains, lactic acid inhibited 97,89% of the strains and peracetic inhibited 100% of the strains. In contaminated chiller water, the compounds reduced the growth of standards strains. When applied to contaminated poultry meat, there was a reduction of Salmonella spp. 1,06 log10 CFU/g relative to the positive control with the use of sodium hypochlorite at 5,0 mg/L, 0,97 log10 CFU/g with dichloro and 0,56 log10 CFU/g with sodium hypochlorite 0,5 mg/L. For mesophiles reduction observed was 0,90 log10 CFU/g relative to the positive control with the use of sodium hypochlorite at 5,0 mg/L, 0,83 log10 CFU/g with dichloro and there isn´t reduction with hypochlorite with sodium 0,5 mg/L. For enterobacteriaceae reduction was 1,0 log10 CFU/g relative to the positive control with the use of sodium hypochlorite at 5,0 mg/L, 0,79 log10 CFU/g with dichloro and 0,22 log10 CFU/g with sodium hypochlorite at 0,5 mg/L. Lactic acid inhibit growth of the microorganisms tested. The data supports the discussions to regulate the use of the technology coadjuvants in the slaughter of poultry.